IRON-ZINC SUPPLEMENTATION AMONG ADOLESCENT GIRLS AT ELEMENTARY SCHOOL IN KUPANG CITY, EAST TIMOR PROVINCE. - Indriastuti Kurniawan, Yustina Anie; Muslimatun, Siti (GIZI INDONESIA, 2005)
Anemia is the main micronutrient deficiency problem among adolescent girls in Indonesia. Anemia due to iron deficiency often coexists with zinc deficiency. Both iron deficiency anemia and zinc deficiency can increase the risk of obstetric complications among pregnant women i.e. bleeding during labor and post-partum hemorrhage. Iron-folate supplementation among pregnant women had been conducting since long time ago throughout this country; however, effort to improve the nutritional status particularly among adolescent girls prior to pregnancy is still lack behind. Iron and zinc have antagonistic interaction. Therefore it was challenging to alleviate anemia problem among adolescent girls with appropriate ratio of iron-zinc supplementation, and will give a benefit to improve their nutritional status. This study was aimed to investigate the different ratios of ironzinc supplementation on reducing the prevalence of anemia as improving the nutritional status of adolescent school girls.A female elementary school students age 10-12 years old (n= 137) were screened in rural area of Kupang City, East Timor Province. Subjects were assigned randomly to one of the three groups for daily iron-zinc supplementation for 12 weeks; Group 1 (iron; 60 mg/day), Group 2 (iron and zinc; 30 mg and 15 mg/day), Group 3 (iron and zinc; 60 mg and 15 mg/day). Hemoglobin concentration was measured by cyanmethemoglobin method (Hemocue) to determine the prevalence of anemia (Hb level < 120 g/L), while anthropometric assessment was conducted for measuring weight and height to determine the nutritional status. General characteristics was assessed through interview. At base line, 29.1% of subjects suffered from anemia and in general, the prevalence was reduced to around 13.1% after they took iron supplements with or without zinc. Hemoglobin concentration was significantly increased among all subjects euther suffered from anemia or not. The result of this study showed that subject who received iron/zinc supplement with ratio 4: 1 for 12 weeks asa “blanket approach” significantly increased hemoglobin conc. higher than to who received iron alone. Similar result occurred when supplement was received to anemic adolescent. Although there were significantly increased of weight, height and BMI for age among all groups, the percentage of subjects were underweight, stunted and wasted remains high after supplementation that 54.6%, 36.9% and 39.2% respectively. Anemia seems to be a health problem among adolescent school girls in Kupang City, East Timor Province and iron-zinc supplementation with appropriate ratio is promising to increase hemoglobin level. A large scale of cohort study was recommended for female student, to investigate the effect iron/zinc supplementation with ratio 2: 1 on iron, zinc status and growth performance among adolescent girls.Key Words: Iron, Zinc, Adolescent, Girls